A tracheal scaffold of gelatin-chondroitin sulfate-hyaluronan-polyvinyl alcohol with orientated porous structure. (1st March 2017) - Yu, Xueping; Qian, Guowen; Chen, Si; Xu, Dong; Zhao, Xiujuan; Du, Chang
Highlights: Orientated porous scaffolds were prepared via a unidirectional freeze-drying method. The orientated scaffolds demonstrated desirable flexibility and viscoelasticity. The orientated scaffolds promoted cell adhesion and ingrowth. Abstract: Scaffold of gelatin-chondroitin sulfate-hyaluronan-polyvinyl alcohol (GCH-PVA) with orientated microtubule structure and good hydrophilicity was fabricated by unidirectional freeze-drying method mimicking the composition and structure of tracheal cartilage extracellular matrix. PVA was incorporated to improve flexibility and viscoelasticity of GCH scaffold. All wet scaffolds showed similar compressive elastic modulus with native cartilage. GCH-PVA scaffolds showed high relative remaining stress during relaxation indicating good mechanical stability. The hysteresis ratio during cyclic compression increased gradually with PVA content and close to native cartilage. During multiple frequency compression, all scaffolds showed a low loss tangent close to native cartilage, and PVA incorporation enhanced the elasticity of scaffolds when they were stressed under high frequency. The incorporation of PVA promoted gene expression of adhesion related integrin α5 β1 and actin by mouse bone marrow mesenchymal stem cells (mBMSCs). With the orientated microtubule structure, cells ingrowth into scaffolds was facilitated by dynamic culture method.